Pengaruh Pengetahuan Produk dan Kepercayaan Konsumen terhadap Minat Beli Produk Segar Melalui Shopee pada Masyarakat Surabaya - Hana Mutiara; Iswati Iswati (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of product knowledge and consumer trust on the interest in buying fresh products through the Shopee e-commerce platform in the people of Surabaya City. The research method used is quantitative with an associative approach. The sample in this study amounted to 96 respondents who were selected using the purposive sampling technique, namely consumers who have purchased fresh products through Shopee in the last three months. Data collection was carried out through an online questionnaire using Google Form, and data analysis was carried out by multiple linear regression tests using the help of SPSS software version 27. The results showed that partially, product knowledge had a negative but significant influence on buying interest, indicating that the higher the consumer's knowledge of fresh products, the more critical they were in considering purchases. Conversely, consumer trust has a positive and significant effect on buying interest, indicating that trust in platforms and products drives purchase decisions. Simultaneously, these two independent variables have a significant effect on buying interest. These findings imply that increasing consumer trust needs to be the main focus of fresh produce marketing strategies in e-commerce, while product information should be presented in a transparent and convincing manner.